2023
DOI: 10.3390/antiox12071324
|View full text |Cite
|
Sign up to set email alerts
|

Alpinumisoflavone Activates Disruption of Calcium Homeostasis, Mitochondria and Autophagosome to Suppress Development of Endometriosis

Abstract: Alpinumisoflavone is an isoflavonoid extracted from the Cudrania tricuspidate fruit and Genista pichisermolliana. It has various physiological functions, such as anti-inflammation, anti-proliferation, and apoptosis, in malignant tumors. However, the effect of alpinumisoflavone is still not known in chronic diseases and other benign reproductive diseases, such as endometriosis. In this study, we examined the cell death effects of alpinumisoflavone on the endometriosis cell lines, End1/E6E7 and VK2/E6E7. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…The ER is a large and dynamic organelle that plays a role in protein synthesis, transport, carbohydrate metabolism, and calcium storage. Moreover, the ER covers approximately 20% of the mitochondrial surface so that both organelles conduct key intracellular functions together, such as regulating cell survival, energy metabolism, and calcium homeostasis [ 27 , 28 , 29 ]. First, in the aspect of calcium homeostasis, there are ryanodine receptors (RyR), IP 3 R, and sarcoendoplasmic reticulum calcium ATPase in the ER membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The ER is a large and dynamic organelle that plays a role in protein synthesis, transport, carbohydrate metabolism, and calcium storage. Moreover, the ER covers approximately 20% of the mitochondrial surface so that both organelles conduct key intracellular functions together, such as regulating cell survival, energy metabolism, and calcium homeostasis [ 27 , 28 , 29 ]. First, in the aspect of calcium homeostasis, there are ryanodine receptors (RyR), IP 3 R, and sarcoendoplasmic reticulum calcium ATPase in the ER membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated the abnormal expression of calcium regulatory molecules in patients with endometriosis, adenomyosis, and UCEC [43,44,45]. These calcium extrusion regulatory molecules in the endometrium encompass plasma membrane Ca 2+ ATPases (PMCAs) and sodium-calcium exchangers SLC8As, which are secreted into the uterine lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Açai Berry administration was able to modulate autophagy, oxidative stress, and apoptosis in mouse endometriosis models [114]. Alpinumisoflavone is an isoflavonoid extracted from fruit that inhibits cell migration and proliferation and leads to cell apoptosis in endometriosis cell lines [115].…”
Section: Rcd Therapeutic Perspectives In Endometriosismentioning
confidence: 99%